2018
DOI: 10.1016/j.ebiom.2018.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Focused Cognitive Therapy for Cocaine Use Disorder: Theory, Procedures and Preliminary Evidence From an External Pilot Randomised Controlled Trial

Abstract: BackgroundCocaine use disorder (CUD) is a debilitating condition with no NICE-recommended medication or specific psychosocial interventions. In the United Kingdom (UK), general counselling (treatment-as-usual; TAU) is widely delivered, but has limited effectiveness. We tested the feasibility, safety and preliminary efficacy of a novel, adjunctive psychosocial intervention for CUD, called ‘memory-focused cognitive therapy’ (MFCT).MethodsWe did a two-arm, external pilot randomised controlled trial at a specialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…If there is an unsatisfactory response to flexible dosing, it may be appropriate to suggest a change in medication (e.g. switching from methadone to buprenorphine), reinstate supervised administration (Clinical Guidelines on Drug Misuse and Dependence Update 2017 Independent Expert Working Group, 2017), or offer a targeted psychosocial intervention for opioids , alcohol (Nolan et al, 2016) or cocaine (Marsden et al, 2018) from the service if there are resources or by referral. Although it may be discouraging that some patients continue to alcohol and other drugs, treatment may still offer provide important harm reduction benefits by reducing the risk of opioid poisoning (Cornish et al, 2010;White et al, 2015) and, taking a wider societal perspective, there is an overall economic benefit-cost ratio from investing in OST (Zarkin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…If there is an unsatisfactory response to flexible dosing, it may be appropriate to suggest a change in medication (e.g. switching from methadone to buprenorphine), reinstate supervised administration (Clinical Guidelines on Drug Misuse and Dependence Update 2017 Independent Expert Working Group, 2017), or offer a targeted psychosocial intervention for opioids , alcohol (Nolan et al, 2016) or cocaine (Marsden et al, 2018) from the service if there are resources or by referral. Although it may be discouraging that some patients continue to alcohol and other drugs, treatment may still offer provide important harm reduction benefits by reducing the risk of opioid poisoning (Cornish et al, 2010;White et al, 2015) and, taking a wider societal perspective, there is an overall economic benefit-cost ratio from investing in OST (Zarkin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, theories describing the contributions of different memory systems to addiction describe both parallel and interactive effects (Table 1). These theories have been extremely influential, inspiring research programs and the development of addiction treatments (recent examples in [11, 12]). With recent evidence that memory for even a single experience can influence later decision-making [13, 14], understanding how memories for drug-related experiences are formed is a critical and timely question.…”
Section: Memories For Drug Usementioning
confidence: 99%
“…Prior to the analysis of the developmental study (Marsden et al, 2018), the statistical analysis plan for the primary and secondary outcome measures was registered (Centre for Open Science; https://www. osf.io/3kfzj/).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the analysis of the developmental study (Marsden et al, 2018), the statistical analysis plan for the primary and secondary outcome measures was registered (Centre for Open Science; https://www.osf.io/3kfzj/). The results showed that compared to an assessment-only control, the intervention was associated with lower levels of craving (bias corrected Hedge’s g = −1.62; 95% confidence interval (CI) −2.45 to –0.80; the primary outcome measure) and more abstinent days ( g = 1.19; 90% CI 0.54 to 1.84; the drug use secondary outcome measure).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation